2008
DOI: 10.1002/cne.21910
|View full text |Cite
|
Sign up to set email alerts
|

Formation and maturation of parallel fiber‐purkinje cell synapses in the staggerer cerebellum ex vivo

Abstract: In vivo, homozygous staggerer (Rorasg/sg) Purkinje cells (PCs) remain in an early stage of development with rudimentary spineless dendrites, associated with a lack of parallel fiber (PF) input and the persistence of multiple climbing fibers (CFs). In this immunocytochemical study we used cerebellar organotypic cultures to monitor the development of Rorasg/sg PF‐PC synapses in the absence of CF innervation. Ex vivo the vesicular glutamate transporters VGluT1 and VGluT2 reactivity was preferentially localized ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 65 publications
2
9
0
Order By: Relevance
“…It has been reported that PFs in sg / sg mice are able to establish a small number of immature junctional complexes onto PC dendrites morphologically, although those synaptic contacts scarcely develop into spine‐shaped mature synapses (Hirano & Dembitzer, 1975; Sotelo, 1975, 1990; Landis & Reese, 1977; Berry et al 1978; Janmaat et al 2009). To assess the functional properties of such PF–PC synapses in staggerer mutant mice, we tried to record PF‐evoked excitatory synaptic responses from voltage‐clamped PCs (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been reported that PFs in sg / sg mice are able to establish a small number of immature junctional complexes onto PC dendrites morphologically, although those synaptic contacts scarcely develop into spine‐shaped mature synapses (Hirano & Dembitzer, 1975; Sotelo, 1975, 1990; Landis & Reese, 1977; Berry et al 1978; Janmaat et al 2009). To assess the functional properties of such PF–PC synapses in staggerer mutant mice, we tried to record PF‐evoked excitatory synaptic responses from voltage‐clamped PCs (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The surviving PCs (∼20%) (Herrup & Mullen, 1981; Doulazmi et al 2001) can form synapses with climbing fibres, although they remain multiply innervated even at adult age because of a failure in the developmental elimination of surplus climbing fibres (Mariani & Changeux, 1980; Steinmayr et al 1998). On the other hand, it has been reported that parallel fibres (PFs) cannot make mature spine‐type functional synapses onto PCs in sg / sg mice (Hirano & Dembitzer, 1975; Sotelo, 1975, 1990; Landis & Reese, 1977; Berry et al 1978; Janmaat et al 2009); however, previous ultrastructural studies also showed that some PFs from remaining granule cells are able to form primitive synapse‐like junctional structures on sg / sg PCs (Sotelo, 1973, 1975, 1990; Hirano & Dembitzer, 1975; Berry et al 1978). It remains unclear whether such primitive junctions function as synapses since detailed electrophysiological investigation has not been performed on PF–PC synaptic transmission in sg / sg mice.…”
Section: Introductionmentioning
confidence: 99%
“…cells (Gö rcs et al, 1993;Hà mori et al, 1996;Knö pfel and Grandes, 2002) were mGlu1a immunopositive. MGlu1 has also been localized in somata and dendrites of the cerebellar Staggerer mouse Purkinje cells in organotypic cultures (Janmaat et al, 2009). Furthermore, we have revealed the subcellular localization of mGlu1a receptor in the organotypic cultures using two different immunocytochemical techniques for electron microscopy.…”
Section: Discussionmentioning
confidence: 96%
“…Labelled with adequate immunohistochemical markers (Enderlin et al, 1987;Weiser et al, 1995;Sekirnjak et al, 1997;Liu and Kaczmarek, 1998;Diñ o et al, 1999;Shibata et al, 1999;Ló pez Bendito et al, 2001;Knö pfel and Grandes, 2002;Bastianelli, 2003;Sacco et al, 2006), cultured cerebellum renders a mixture of preserved (Janmaat et al, 2009) and altered features. Despite the lack of the extrinsic climbing and mossy fibres, the immunohistochemical characteristics and morphology of the granule and Golgi cells were maintained in our cultures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation